Greetings from Tobago - (:unkn) unknown (H.O. Thomas, [Trinidad and Tobago], 2011)
Description printed on the back of the postcard: "Store Bay, one of Tobago's most popular bathing resorts."
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Leisure--Trinidad and Tobago; Bays--Trinidad and Tobago